PERSEPSI MASYARAKAT TERHADAP KESENIAN KUDA LUMPING DI DESA BATANG BATINDIH KECAMATAN RUMBIO JAYA KABUPATEN KAMPAR - Riyan Turniadi; Jonyanis " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
The purpose of this study was to determine the public perception of the arts kuda lumping in the village of Batang Batindih Rumbio Jaya District of Kampar, and to know what the cause of the reduced interest in art kuda lumping in the village of Batang Batindih Rumbio Jaya subdistrict Kampar.Perkembangan arts district kuda lumping contained in the village of Batang Batindih very fast, the beginning of the influx of art lumping horse was brought by the community of Java that comes from transmigration, the community is very enthusiastic in jazz performing arts kuda lumping, because for them the art lumping horse is one of the cultural heritage that must be preserved and maintained. However, along with the development of the times and also science, society begins to feel bored with the art that most people prefer to look for other entertainment such as a single organ is more modern and more attractive. This type of research used was descriptive integrates mixed method approach is a combination of quantitative and qualitative research in a variety of research process (design, a data collection and analysis of data) in order to provide a better understanding of an issue of research. The research location is in the village of Batang Batindih, with the number of sample were 63 people, and informants in this study is the Javanese society transmigration as many as five people including village officials, community leaders, religious leaders, the chairman of the management group lumping horse and the man who had invited leathered horse.The results were obtained some conclusions are quite good public perception of the arts lumping horse in the village of Batang Batindih Rumbio Jaya District of Kampar regency. Community leaders consider that lumping horse art is an art that can be used as entertainment for the local community. The arts are considered public attention through the attractions of the supernatural. Religious leaders assume that art is a less good art, because it highlights the performing arts kuda lumping sometimes followed by liquor. The majority of young people consider that lumping horse art is not interesting to watch. Decreased interest in art kuda lumping in the village of Batang Batindih Kampar Jaya subdistrict Rumbio resulting transition has occurred culture, people believe that art kuda lumping impractical and inefficient.Keywords: Public Perception, Art Kuda Lumping